Comparison Of Stretching And Cold Water Immersion With Stretching And Water Contracts In Reducing Athletic Pain - Ainul Ghurri, Ainul Ghurri; Atmaja, Danuditya Purna; Hafizah Sururul Nur Rakhmawati; Ifa Gerhanawati (UNIB Press, 2024)
Athletes often experience muscle pain called delayed onset muscle soreness (DOMS) after strenuous exercise that overloads the muscles, symptoms that arise in the form of muscle pain, muscle cramps, muscle weakness, and even can cause muscle tissue tears. This study aimed Their qualifications and experience intervention was better for reducing DOMS pain in athletes running as far as 3000 meters. The research was carried out in the athletics field, experimental in nature with a pretest and posttest two-group design. Male athletes were divided into two groups of nine each and underwent interventions to assess changes in pain tolerance after a 3000-meter run. Group I experienced a significant increase in pain tolerance after 48 hours following an intervention combining stretching and coldwater immersion. Similarly, Group II showed a significant increase in pain tolerance after the same timeframe with an intervention combining stretching and regular water immersion. However, statistical analysis revealed that the intervention involving cold water immersion (Group I) was more effective in reducing Delayed Onset Muscle Soreness (DOMS) compared to the regular water immersion (Group II).